Resolving Conflict Emotions: Strategies for Enhancing Environmental Communication and Public Engagement on Social Media from a Communication Semiotics Perspective — A Case Study of the Red Platform - Tianqi Zhuang (Jurnal Audiens, 2024)
This study uses grounded theory to explore the dynamic interaction between social media discourse and public attitudes towards environmental issues, especially in the context of opinion differentiation and information cocoons. By analyzing the conversations of Generation Z users on the Chinese social media platform Xiaohongshu, this study investigated the acceptance of environmental information and discussed strategies to enhance public participation in environmental sustainability. Through the rigorous process of open coding, spindle coding and selective coding, a structure diagram is constructed to promote open dialogue and coordinate diverse perspectives to overcome scepticism about environmental protection and to promote active public action on environmental protection. This study emphasizes that social media has certain potential in promoting effective public communication on environmental protection issues.